Restoration of metabolic health by decreased consumption of branched‐chain amino acids. (27th December 2017) - Cummings, Nicole E.; Williams, Elizabeth M.; Kasza, Ildiko; Konon, Elizabeth N.; Schaid, Michael D.; Schmidt, Brian A.; Poudel, Chetan; Sherman, Dawn S.; Yu, Deyang; Arriola Apelo, Sebastian I.; Cottrell, Sara E.; Geiger, Gabriella; et al.
Abstract : Key points: We recently found that feeding healthy mice a diet with reduced levels of branched-chain amino acids (BCAAs), which are associated with insulin resistance in both humans and rodents, modestly improves glucose tolerance and slows fat mass gain. In the present study, we show that a reduced BCAA diet promotes rapid fat mass loss without calorie restriction in obese mice. Selective reduction of dietary BCAAs also restores glucose tolerance and insulin sensitivity to obese mice, even as they continue to consume a high‐fat, high‐sugar diet. A low BCAA diet transiently induces FGF21 (fibroblast growth factor 21) and increases energy expenditure. We suggest that dietary protein quality (i.e. the precise macronutrient composition of dietary protein) may impact the effectiveness of weight loss diets. Abstract: Obesity and diabetes are increasing problems around the world, and although even moderate weight loss can improve metabolic health, reduced calorie diets are notoriously difficult to sustain. Branched‐chain amino acids (BCAAs; leucine, isoleucine and valine) are elevated in the blood of obese, insulin‐resistant humans and rodents. We recently demonstrated that specifically reducing dietary levels of BCAAs has beneficial effects on the metabolic health of young, growing mice, improving glucose tolerance and modestly slowing fat mass gain. In the present study, we examine the hypothesis that reducing dietary BCAAs will promote weight loss, reduce adiposity, and improve blood glucose control in diet‐induced obese mice with pre‐existing metabolic syndrome. We find that specifically reducing dietary BCAAs rapidly reverses diet‐induced obesity and improves glucoregulatory control in diet‐induced obese mice. Most dramatically, mice eating an otherwise unhealthy high‐calorie, high‐sugar Western diet with reduced levels of BCAAs lost weight and fat mass rapidly until regaining a normal weight. Importantly, this normalization of weight was mediated not by caloric restriction or increased activity, but by increased energy expenditure, and was accompanied by a transient induction of the energy balance regulating hormone FGF21 (fibroblast growth factor 21). Consumption of a Western diet reduced in BCAAs was also accompanied by a dramatic improvement in glucose tolerance and insulin resistance. Our results link dietary BCAAs with the regulation of metabolic health and energy balance in obese animals, and suggest that specifically reducing dietary BCAAs may represent a highly translatable option for the treatment of obesity and insulin resistance. Key points: We recently found that feeding healthy mice a diet with reduced levels of branched-chain amino acids (BCAAs), which are associated with insulin resistance in both humans and rodents, modestly improves glucose tolerance and slows fat mass gain. In the present study, we show that a reduced BCAA diet promotes rapid fat mass loss without calorie restriction in obese mice. Selective reduction of dietary BCAAs also restores glucose tolerance and insulin sensitivity to obese mice, even as they continue to consume a high‐fat, high‐sugar diet. A low BCAA diet transiently induces FGF21 (fibroblast growth factor 21) and increases energy expenditure. We suggest that dietary protein quality (i.e. the precise macronutrient composition of dietary protein) may impact the effectiveness of weight loss diets.